2018
DOI: 10.25115/ejrep.v16i44.1937
|View full text |Cite
|
Sign up to set email alerts
|

La relevancia de la formación y el contacto previo en la opinión de estudiantes universitarios sobre las personas con trastorno mental

Abstract: Introducción. En la presente investigación, se han analizado las diferencias en la opinión de los estudiantes universitarios hacia las personas con trastorno mental, en función de estos si han mantenido un contacto previo con las mismas y si han recibido formación en relación a ellas.Método. Se aplicó la Escala de Opiniones sobre la Enfermedad Mental en Población Española (OMI-E) a una muestra de 474 estudiantes de la Universidad de Extremadura (España), a los que se preguntó si habían mantenido dicho contacto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…In terms of closeness to people with mental health problems, studies report a tendency to stigmatise less in the case of those who have had some kind of contact with mental health. In the general population, knowing someone with psychological problems is associated with better attitudes, lower levels of authoritarianism, less stereotyping, and less desire for social distance Barroso-Hurtado & Mendo-Lázaro, 2018). In a study among high school students, those who had no previous contact showed significantly higher scores on fear and segregation attitudes (García-Soriano & Roncero, 2017).…”
Section: Closeness and Own Experiencementioning
confidence: 99%
See 1 more Smart Citation
“…In terms of closeness to people with mental health problems, studies report a tendency to stigmatise less in the case of those who have had some kind of contact with mental health. In the general population, knowing someone with psychological problems is associated with better attitudes, lower levels of authoritarianism, less stereotyping, and less desire for social distance Barroso-Hurtado & Mendo-Lázaro, 2018). In a study among high school students, those who had no previous contact showed significantly higher scores on fear and segregation attitudes (García-Soriano & Roncero, 2017).…”
Section: Closeness and Own Experiencementioning
confidence: 99%
“…Regarding the participants, most articles deal with samples of the general population (Aznar-Lou et al, 2016;García-Galindo et al, 2012;González-Sanguino et al, 2019;Lahera et al, 2019;Mogollón-Rodríguez et al, 2014;Olafsdottir & Pescosolido, 2011;Ruiz et al, 2012), nursing or medical health professionals (Aragonès et al, 2011;Castillejos-Anguiano et al, 2019;García-Galindo et al, 2012;Guerrero-Díaz et al, 2021), mental health professionals (Del Olmo-Romero et al, 2019) or university students in health degrees (Failde et al, 2014;González-Sanguino et al, 2019;Granados-Gámez et al, 2016;Masedo et al, 2021;O'Ferrall-González et al, 2020;Rodríguez-Almagro et al, 2019) or other degrees (Barroso-Hurtado & Mendo-Lázaro, 2018;Gallego et al, 2020). There are also studies with family members of people with a diagnosis (Ahmedani et al, 2013;Domínguez-Martínez et al, 2014;Revilla et al, 2010) and people with mental health problems (Domínguez-Martínez et al, 2014;García-Galindo et al, 2012;Muñoz et al, 2011).…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
“…It could be thought that knowledge or contact alone would not be enough to reduce stigma. In fact, there are authors who claim that offering information without strategies aimed at contact can increase stigma instead of decreasing it (Fresán et al, 2012), while other authors find that prior contact would generate a change in opinion towards people with mental disorders if it is established when they have already received or are receiving training related to mental health (Barroso-Hurtado & Mendo-Lázaro, 2018). This is why it would be necessary to design intervention programmes that include both variables.…”
Section: Discussionmentioning
confidence: 99%
“…Various works of research have proved that there exist differences in the attitudes towards persons with a disability with respect to the condition of having contact with them or not [19,51,52]. It is with good reason that programs aimed at changing attitudes to disability stress contact with persons with a disability in order to achieve a positive change in the evaluation of terms referring to persons with a disability and, consequently, in attitudes towards them [31,53].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some studies examined the effect that contact with disabled people would have on attitudes, in the sense of generating more positive attitudes towards persons with a disability [30]. On the basis of Allport's Contact Theory [7], numerous authors have pointed out the influence of strategies based on social contact and education when generating positive attitudes and reducing the stigmatization of persons with a disability [31].…”
Section: The Present Studymentioning
confidence: 99%